PENGEMBANGAN MEDIA PEMBELAJARAN BOOKLET PADA MATA PELAJARAN IPS MATERI PRAAKSARA DAN ASAL USUL NENEK MOYANG BANGSA INDONESIA KELAS VII - Zahrotun Nur Hasanah; Dewa Agung Gede Agung (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
ABSTRACT The topic of the Prehistoric Period and the Origins of the Indonesian Ancestors requires students to comprehend historical events that cannot be directly observed, making learning media capable of visualizing abstract concepts an essential component of the instructional process. Preliminary observations conducted in Class VII G of SMP Negeri 2 Malang revealed that classroom instruction still relied predominantly on the whiteboard, resulting in students experiencing difficulties in understanding the subject matter. In response to this issue, the present study developed an illustrated booklet as a learning medium and evaluated its feasibility for use in social studies instruction. The product was developed using a Research and Development (R&D) approach based on the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The study involved one media expert, one subject-matter expert, one social studies teacher, and 32 seventh-grade students. Data were collected through observations, interviews, and questionnaires and were analyzed using the Likert and Guttman scales. The validation results indicated scores of 95% from the media expert and 92.5% from the subject-matter expert, both of which were classified as highly valid. Furthermore, the teacher's response reached 95%, while the students' response achieved 88.4%, indicating that the developed media was highly practical. A distinctive feature of the product is its integration of printed and digital booklet formats through a Quick Response (QR) Code, providing a feasible and practical alternative for social studies learning at the junior high school level. ABSTRAK Materi Praaksara dan Asal Usul Nenek Moyang Bangsa Indonesia menuntut peserta didik memahami peristiwa yang tidak dapat diamati secara langsung sehingga penyajiannya memerlukan dukungan media yang mampu memvisualisasikan konsep secara lebih konkret. Temuan awal di kelas VII G SMP Negeri 2 Malang menunjukkan bahwa pembelajaran masih bertumpu pada penggunaan papan tulis, yang berdampak pada terbatasnya pemahaman peserta didik terhadap materi. Berangkat dari kondisi tersebut, penelitian ini menghasilkan media pembelajaran berupa booklet bergambar yang dirancang untuk mendukung pembelajaran IPS sekaligus menguji kelayakan penggunaannya. Pengembangan produk dilaksanakan melalui pendekatan Research and Development (R&D) dengan model ADDIE yang mencakup tahap Analysis, Design, Development, Implementation, dan Evaluation. Proses penelitian melibatkan seorang ahli media, seorang ahli materi, seorang guru IPS, serta 32 peserta didik kelas VII G. Data dihimpun melalui observasi, wawancara, dan angket, kemudian dianalisis menggunakan skala Likert dan Guttman. Hasil validasi menunjukkan persentase 95% dari ahli media dan 92,5% dari ahli materi yang keduanya berada pada kategori sangat valid. Sementara itu, respons guru mencapai 95% dan respons peserta didik sebesar 88,4% sehingga media tergolong sangat praktis. Keunggulan produk terletak pada integrasi booklet cetak dan digital melalui Quick Response (QR) Code, sehingga menyediakan alternatif media pembelajaran IPS yang layak digunakan pada jenjang SMP.